(untitled) (Eurasian Scientific Herald, 2025)
This article focuses on considering the theoretical aspects of the development of cognitive educational universal actions in primary school students through interactive teaching methods is not only to arm students with a large amount of knowledge, but also to help the modern student develop and improve himself in all aspects by forming universal methods of action in them. Also, using this process, it is to familiarize the student with the environment, the world in a constantly changing society, to teach him to understand life consistently